Chitosan-collagen scaffolds can regulate the biological activities of adipose mesenchymal stem cells for tissue engineering - Zotarelli Filho, Idiberto José [UNESP]; Frascino, Luiz Fernando; Greco, Oswaldo Tadeu; Araújo, José Dalmo de; Bilaqui, Aldemir; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Herbert Publications, 2013)
Scaffolds of chitosan and collagen can offer a biological niche for the growth of adipose derived stem cells (ADSC). The objective of this work was to characterize the physico-chemical properties of the scaffolds and the ADSC, as well as their interactions to direct influences of the scaffolds on the behavior of ADSC. The methodology included an enzymatic treatment of fat obtained by liposuction by collagenase, ASDC immunophenotyping, cell growth kinetics, biocompatibility studies of the scaffolds analyzed by the activity of alkaline phosphatase (AP), nitric oxide (NO) determination by the Griess-Saltzman reaction, and images of both optical and scanning electron microscopy of the matrices. The extent of the crosslinking of genipin and glutaraldehyde was evaluated by ninhydrin assays, solubility tests and degradation of the matrices. The results showed that the matrices are biocompatible, exhibit physical and chemical properties needed to house cells in vivo and are strong stimulators of signaling proteins (AP) and other molecules (NO) which are important in tissue healing. Therefore, the matrices provide a biological niche for ADSC adhesion, proliferation and cells activities.
Keywords: Chitosan-collagen-genipin scaffolds; ADSC; macrophages; biological niche